2013
DOI: 10.1007/s00384-013-1684-y
|View full text |Cite
|
Sign up to set email alerts
|

Current status of laparoscopic surgery for patients with Crohn’s disease

Abstract: In experienced centers, laparoscopic surgery for Crohn's disease is safe and as feasible as open operations, even for selected cases with operations for complicated or recurrent disease. However, accurate analysis of the data is complicated by the heterogeneity of clinical presentations as well as the variety of performed procedures. Additional long-term data are needed for evaluation of true benefits of the new techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…When compared with conventional open surgery, the benefits of laparoscopic surgery have been widely investigated and confirmed in Crohn's disease. [13][14][15][16][17][18] In this study the length of incision of open surgery was much longer than that of laparoscopic surgery 10.31±1.78 vs 5.01±1.24. blood loss (ml) was less in laparoscopic surgery as compare to open surgery.…”
Section: Discussionmentioning
confidence: 55%
“…When compared with conventional open surgery, the benefits of laparoscopic surgery have been widely investigated and confirmed in Crohn's disease. [13][14][15][16][17][18] In this study the length of incision of open surgery was much longer than that of laparoscopic surgery 10.31±1.78 vs 5.01±1.24. blood loss (ml) was less in laparoscopic surgery as compare to open surgery.…”
Section: Discussionmentioning
confidence: 55%
“…The present study demonstrated those benefits as well, including reducing intraoperative blood loss and length of incision, speeding postoperative recovery, shortening hospital stay, and reducing surgical-related complications, especially incision-associated complications. Meanwhile, there were still disadvantages for laparoscopic surgery in CD [ 27 ], such as requiring experienced laparoscopic surgeons and skills, increased cost and time, and not being suited for patients with severe complications and intra-abdominal adhesions.…”
Section: Discussionmentioning
confidence: 99%
“…Application for complex disease remains a controversial topic because complicated anatomy with fistulas or abscesses might make the laparoscopic approach challenging especially for novice laparoscopist. 7 Laparoscopic surgery is favored because it provides benefits such as shorter operative time and better cosmetic results when compared with open surgery. Lower degree of adhesion formation after laparoscopic surgery compared with open surgery 8 could be another beneficial property for complex Crohn's disease patients in the short and long term.…”
Section: Laparoscopic Approachmentioning
confidence: 99%